Sleep promotion for hospitalised children: Developing an evidence-based guideline for nurses - Elijeshca C. Crous; Natasha North (AOSIS, 2021)
Background: Adequate sleep in hospitalised children is important for a variety of physiological and psychological processes associated with growth, development, and recovery from illness and injury. Hospitalisation often prioritises clinical care activities at the expense of age-appropriate sleep. Nurses and the wider healthcare team contribute to this paradox. However, through conscious practice and partnering with mothers, nurses are able to enact change and promote sleep. Objectives: To adopt, adapt or contextualise existing guidelines to develop an evidence-based practice guideline to promote sleep-friendly ward environments and routines facilitated by nurses, and in partnership with mothers. Method: A six-step methodology for guideline adaptation was followed, as recommended by the South African Guidelines Excellence project: (1) existing guidelines and protocols were identified and (2) appraised using the AGREE II instrument; (3) an evidence base was developed; (4) recommendations were modified, (5) assigned levels of evidence and grades of recommendation; and (6) end user guidance was developed. Expert consultation was sought throughout. Results: Existing relevant guidance comprised 61 adult-centric recommendations. Modification of the evidence base led to six composited recommendations that facilitate sleep in hospitalised children: (1) prioritising patient safety; (2) collaborating with the mother or caregiver to promote sleep; (3) coordinating ward routine and (4) environment to improve sleep; (5) work with clinical and non-clinical staff; and (6) performing basic sleep assessments. Practice recommendations were aligned to the South African regulatory framework for nursing. Conclusion: Hospitalisation is a time of physiological and psychological dysregulation for children, which is amplified by poor sleep in a hospital. Nurses have the opportunity to promote sleep during hospitalisation by implementing this African-centric guideline in partnership with mothers.